The detour of the elephants - Garretson, Dee; Lee, J. M. (Joseph M.) (Boxcar children great adventure, 2017)
After solving riddles from the secretive Reddimus Society to figure out their destination, the four Alden siblings fly to China, where they deliver an artifact at the Great Wall, but when they are next rushed to an elephant sanctuary in Thailand, the Aldens suspect they have been tricked and take extra precautions against their enemies.